Evaluasi Sistem Pengendalian Internal Pada Rumah Sakit PKU Muhammadiyah Nanggulan - Rigel Nurul Fathah; Muhammad Khozin (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2018)
This community service was carried out in collaboration with PKU Nanggulan Hospital with Aisyiyah University in Yogyakarta. Previously the team coordinated and need assessment so that it was known the condition of PKU Nanggulan Hospital through observation and interviews with the management of PKU Nanggulan Hospital as well as sharing about what obstacles faced by the management of PKU Nanggulan Hospital so far. Based on observations and direct interviews with partners found problems encountered are weak internal control at PKU Nanggulan Hospital, weaknesses include: (1) There is no separation of duties between gauze, financial and bookkeeping sections (2) There is no Standard Operating Procedure (SOP ) that is clear between parts (3) The absence of a clear job description between parts (4) Financial recording is still simple using cash basis so that it only records cash income and expenses. this service has a program that is expected to be a solution to the problems experienced by partners. The solution program offered is training and socialization, namely giving understanding to management in the form of training and outreach to the management of PKU Nanggulan Hospital regarding the importance of Internal Control in order to improve performance so that it can provide good health services, have relevant and accurate information, and human resources the professional.